(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
The article explores issues related to the investigation of the sociocultural aspects of language through the General Verbal Interpretation Variable and the Sociocultural Verbal Interpretation Variable. It argues that the primary role of the General Verbal Interpretation Variable is to activate collective knowledge represented by language as a system. In contrast, the function of the Sociocultural Verbal Interpretation Variable is to highlight the mental models of individual knowledge that speakers use in discourse. This study builds on previous research and employs a specially developed methodology called Cognitive-Discursive Interpretant (CDI) analysis, providing new insights into how the Sociocultural Verbal Interpretation Variable is triggered by meta-concepts such as ROLES, STEREOTYPES, VALUES, NORMS, SPACE, TIME, and LANGUAGE PERFORMANCE. These universal knowledge structures shape the sociocultural diversity of any language. The findings offer valuable insights into the socio-cognitive framework of linguistics, examining the interplay of society, culture, thought, language, and the human mind, aligning with the general, cognitive, and interpretive principles of the cognitive approach.